Cancer‐associated fibroblasts: Key players in shaping the tumor immune microenvironment. Issue 1 (1st June 2021) - Desbois, Mélanie; Wang, Yulei
Abstract: Cancer immunotherapies have rapidly changed the therapeutic landscape for cancer. Nevertheless, most of the patients show innate or acquired resistance to these therapies. Studies conducted in recent years have highlighted an emerging role of cancer‐associated fibroblasts (CAFs) in immune regulation that shapes the tumor immune microenvironment (TIME) and influences response to cancer immunotherapies. In this review, we outline recent advances in the understanding of phenotypic and functional heterogeneity of CAFs. We will focus on emerging roles of CAFs in shaping the TIME, especially under a framework of tumor immunity continuum, and discuss current and future CAF‐targeting therapeutic strategies in particular in the context of optimizing the success of immunotherapies.